Random sums of random vectors and multitype families of productive individuals - I. Rahimov; H. Muttlak (International Journal of Mathematics and Mathematical Sciences)
We prove limit theorems for a family of random vectors whose coordinates are a special form of random sums of Bernoulli random variables. Applying these limit theorems, we study the number of productive individuals in n-type indecomposable critical branching stochastic processes with types of individuals T1,…,Tn.